Interpreting the function of cell penetrating peptide (RGD) in drug transport to the cell membrane: a computational approach - Fatemeh Talaei; Farzaneh Farzad (Scientific Reports)
Abstract Carbon nanotubes (CNT) have unique properties that make them an excellent option for use as drug carriers. However, to make them safe for the human body, their walls are typically coated with a layer of peptide, which also helps to neutralize their toxicity. Additionally, a specific peptide sequence can be used to deliver therapeutic agents exclusively to cancer cells. In recent years, considerable progress has been made in the development of drug delivery systems (DDS) for drug delivery by computer-assisted. The present study inquires about the loading of ketoprofen (Ket) and naproxen (Nap) conjugated with RGD peptide sequence on CNT and its interaction with the double-layer membrane using the molecular dynamics (MD) simulation method. The obtained results show that the investigated complexes often interact through van der Waals and π-π interactions. Energy values for ketoprofen and naproxen with CNT were evaluated − 270.63 and − 195.8 kJ/mol, respectively. The results of the physical adsorption of the complexes on the membrane surface show that the CNT-KRG and CNT-NRG complexes spontaneously diffuse into the biological membrane. In addition, the study of the interaction energy values ​​of these two complexes with the membrane shows that the van der Waals energy plays a significant role in the stability of the systems. On the other hand, the study of the interaction between the drug-CNT complex and the membrane surface shows that the drug can easily penetrate the membrane in the presence of the peptide sequence and the carrier.